Amino acid profiles, disease activity, and protein intake in adult patients with Crohn’s disease - Cioffi, Iolanda; Di Vincenzo, Olivia; Imperatore, Nicola; Fisco, Mariagrazia; Testa, Anna; Scialò, Filippo; Castiglione, Fabiana; Ruoppolo, Margherita; Pasanisi, Fabrizio; Santarpia, Lidia (Frontiers in Nutrition, 2023)
Crohn's disease (CD) is an immune-mediated inflammatory disorder of the gastrointestinal tract with a relapsing-remitting course. Amino acids (AAs) may play critical roles in the intestinal manifestations of disease, due to their involvement in many metabolic and immune functions. The present study aimed to explore serum AAs concentrations in adult patients with CD, looking into their variations due to disease activity, surgery and protein content of diet. Eventually, the link between AAs and inflammatory markers was also assessed. Consecutive adult patients aged 18-65 years with diagnosis of CD were recruited. All participants underwent anthropometry and were instructed to fill in a 3-day food record to assess protein intake. Disease activity was clinically defined using the Crohn's Disease Activity Index (CDAI), while blood samples were taken to analyze serum AA profile and inflammatory markers. A total of 103 patients with CD (61 men and 42 women; age:39.9±13.9 years, BMI: 23.4±3.51 kg/m 2 ) were included. Tryptophan levels were found to be remarkably decreased in most subjects, unrelated to disease activity. On the contrary, concentration of lysine (Lys), leucine (Leu), valine (Val) and glutamine (Gln) decreased in active versus quiescent CD patients, while aspartic acid (Asp), glutamate (Glu) and glycine (Gly) increased. The latter AAs were also directly correlated with CDAI and serum interleukin (IL)-1β concentration. Considering the total protein intake of patients, expressed as g/kg/body weight, we observed a reduction in some essential AAs (EAAs) in those patients with unmet protein requirements intakes Codice campo modificato 2 This is a provisional file, not the final typeset article compared to patients who met meeting the generalthe recommendation. In conclusion, specific AAs varied according to disease activity and different protein intake, adjusted toper body weight and disease status. Additionally, Glu and Asp concentrations raised with increasing IL-1β. However, extensive research is needed to understand the mechanisms underpinning the link between variation in serum AAs, disease activity and protein intake in patients with CD.